“Confusions about the place and the way in which I grew up”: Place and Knowledge in Joan Didion’s Memoir Where I Was From - Wagner, Alexandra (Current Objectives of Postgraduate American Studies, 2012)
This essay is a close reading of Joan Didion’s memoir Where I Was From“ (2003), and it is particularly focused on the spatial aspects of Didion’s narrative. I am arguing that the production of autobiographical knowledge in this text is closely linked to the places the narrator is referring to and in which she positions herself. Furthermore, this essay aims at illustrating that Didion’s narrative itself functions as a genre-specific site for the production of autobiographical knowledge.